Socio-economic factors associated with post-traumatic stress symptoms among adolescents and young people during the first wave of the COVID-19 pandemic - Folayan, MO; Abeldaño Zuñiga RA; Ellakany, P; Yousaf, MA; Osamika, BE; Virtanen, JI; Gaffar, B; Lawal, FB; Khalid, Z; Aly, NM; Lusher, J; Nguyen, AL (United Kingdom, 2025)
This study assessed the association between sociodemographic factors and post-traumatic stress symptoms (PTSS) among 18-24-year-olds during the first wave of the COVID-19 pandemic. This was a secondary analysis of data from 4508 individuals collected through an online survey conducted between June and January 2021. PTSS was measured as a dependent variable using the checklist for post-traumatic stress disorder in civilians. Age, birth sex, sexual, level of education, access to emotional and social support, and emotional distress were the independent variables. A multivariate logistic regression analysis was conducted to determine the associations between the dependent and independent variables while controlling for the country related confounding variables. Females (AOR:2.023), sexual minority individuals (AOR:1.868), those who did not disclose their sexual identify (AOR:1.476), those with poor access to emotional and social support (AOR:4.699) and individuals with no formal education (AOR:13.908), and only primary level education (AOR:4.521) had higher odds of PTSS. The study highlights the multifaceted nature of PTSS during the pandemic and suggests the importance of promoting access of young people, especially females, sexual minority individuals and those with low educational status, to emotional/social support to mitigate the probability of PTSS, especially among sexual minority individuals.